On interrogative utterances in Croatian and Czech - Sesar, Dubravka (Array, 1998)
Due to the fact that Croatian and Czech are related and typologicaly close Slavic languages, it can be claimed that they do not differ substantially in the construction of interrogative utterances. This article contretates therefore, on the communicational problems relatet to the particular functions of various questin types.